4.0k views
3 votes
Solve −2(2x + 5) − 3 = −3(x − 1)

User Jasdeep
by
5.1k points

2 Answers

2 votes

Answer:

x= -16

Explanation:

distribute -2

-2 * 2x =-4x

-2 * 5 = -10

-4x - 10 -3 = -3 (x-1)

distribute -3

-3 * x = -3x

-3 * -1 = 3

-4x - 10 -3 = -3x + 3

combine like terms

-4x -13 = -3x + 3

-4x + 3x = -x

3 + 13 = 16

-x = 16

divide by -1

x = -16

User Andraaspar
by
5.1k points
6 votes

Answer:

x = -16

Explanation:

-2(2x + 5) - 3 = -3(x - 1)

-4x - 10 - 3 = -3x + 3

-4x - 13 = -3x + 3

-x = 16

x = -16 <--- This is the answer

Hope this helps!

User XaxD
by
5.6k points